Evaluasi Perbandingan Informasi Citra MRI Brain Sekuen Diffusion Weighted Imaging Irisan Axial Pada Variasi Nilai SENSE di Instalasi Radiologi RSUD Provinsi NTB - I Made Lana Prasetya; I Bagus Gede Dharmawan; I Wayan Ariec Sugiantara; Nandika A.J Mokoagow (STIKes Ibnu Sina Ajibarang, 2023)
Magnetic Resonance is a radiodiagnostic examination tool in the field of radiology, especially in the medical world. Diffusion Weighted Imaging is a method to assess molecular function and microarchitecture of the human body. DWI signal contrast can be measured with visible diffusion coefficient maps and serves as a tool for treatment response evaluation and disease progression assessment. Parallel imaging techniques involve phased array coils to process signals from a slice, then combine these slices to form an image, reducing scan time by reducing the acquired K-space lines. The formation of Sensitivity Encoding (SENSE) can shorten the insertion of K-space. This study aims to test variations of SENSE values 2.0 and 2.5 in MRI brain examinations with axial DWI sequences that are capable of visualizing anatomical information with fast scan times without compromising image quality, resulting in optimal images. This research is quantitative with an experimental approach. The sample consists of 10 patients using voluntary sampling of MRI Brain with axial DWI sequence and varying SENSE values from July to August 2023. Data were collected through questionnaires filled out by three radiology specialists at the Radiology Installation of the Provincial Hospital of West Nusa Tenggara (RSUD Provinsi NTB). The results of the Wilcoxon test showed a significant difference in anatomical information in MRI brain with axial DWI sequences between SENSE values of 2 and 2.5, with a p-value of 0.012. The mean rank value results indicated a sum of ranks of 280.00 for the SENSE 2 value, demonstrating greater optimality compared to SENSE 2.5. This study concludes that there is a significant difference in anatomical information in MRI brain with axial DWI sequences between SENSE values of 2 and 2.5. SENSE 2 tends to provide more optimal information.